Early metabolic response in sequential FDG-PET/CT under cetuximab is a predictive marker for clinical response in first-line metastatic colorectal cancer patients: results of the phase II REMOTUX trial - Berger, Anne Katrin; Haag, Georg Martin; Grüllich, Carsten; Dietrich, Mareike; Apostolidis, Leonidas; Giesel, Frederik L.; Weber, Tim; Haberkorn, Uwe; Jäger, Dirk (British journal of cancer, 2018)
To assess the predictive value of early metabolic response (ΔSUV) after short-term treatment with first-line cetuximab in patients (pts) with RAS-wt metastatic colorectal cancer (mCRC). In this prospective phase II study, RAS-wt mCRC pts received a single-agent cetuximab run-in therapy of 2 weeks. ΔSUV was assessed with FDG-PET/CT on days 0 and 14. Early clinical response (ECR) was evaluated with CT on day 56 after treatment with FOLFIRI-cetuximab. Primary endpoint was the predictive significance of ΔSUV for ECR. Secondary endpoints were PFS (progression free survival), OS and the influence of ΔSUV on survival. Forty pts were enroled and 33 pts were evaluable for the primary endpoint. The CT response rate was 57.6%. For responders, ΔSUV was significantly higher (p = 0.0092). A significant association of ΔSUV with ECR was found (p = 0.02). Median PFS was 11.7 months and median OS was 33.5 months with a 1-year survival rate of 87.9%. ΔSUV was found to significantly impact the hazard for OS (p = 0.045). We demonstrate that cetuximab induces metabolic responses in mCRC pts. The study endpoint was met with the ΔSUV discriminating between responders and non-responders. However, these data should be validated in larger patient cohorts.
Gesehen am 06.05.2019